Community-based newborn care utilization and associated factors in Nekemte City, Oromia, Ethiopia, 2023 - Dawit Tesfaye Daka; Bizuneh Wakuma; Werku Etafa; Dereje Temesgen Chewaka; Ashenafi Zewdie; Mekdelawit Birhanu Ayele; Yohannis Midekso Beriso; Bruck Tesfaye Legesse; Wandimu Muche Mekonen (BMC Pediatrics)
Abstract Background Community-Based Newborn Care [CBNC] program aims to improve the health of the newborns. Despite management improvements, many young infants with serious bacterial infections [PSBI] in resource-limited settings are not receiving recommended inpatient treatment due to accessibility, affordability, or family acceptance issues. Therefore, this study aimed to assess the level of CBNC utilization and associated factors among women who delivered recently their newborns in Nekemte city, West Oromia, Ethiopia. Methods A community-based cross-sectional study design was carried out. A two-month infants’ mother interview was conducted from March 1 to April 30, 2023, using data from 556 mothers in Nekemte city. Nurses trained and working in this city collected the data. Data were collected using Kobo Toolbox software and exported to STATA Version 14 for analysis. A binary logistic regression analysis was carried out. In the multivariable logistic regression analysis, a p value of < 0.05 and adjusted OR [AOR] with a 95% CI were used to identify factors statistically associated with CBNC service utilization. Result The overall level of community based care utilization was 35.25% [95% CI: 33.85–44.60]. While time of first anti natal care contacts [AOR: 0.14; 95% CI: 0.08–0.25], maternal age [AOR: 3.36; 95% CI: 1.35–8.31], marital status [AOR: 0.24; 95% CI: 0.08–0.75], and estimated wealth level [AOR: 6.54; 95% CI: 2.24–19.11] were significantly associated factors with the level of community-based utilization of newborn care. Conclusion Community-based newborn care utilization was low from the study area in related to the previous studies and national recommendation. Therefore, creating awareness for mothers to start their antenatal contacts early or at the first trimester, giving information about community-based utilization of newborn care services to teenagers, and supporting mothers who are widowed and of medium or high income to use the community-based utilization of newborn care services.